Clinical Outcome and Safety of Transcaval Access for Transcatheter Aortic Valve Replacement as Compared to Other Alternative Approaches - Barbash, Israel M.; Segev, Amit; Berkovitch, Anat; Fefer, Paul; Maor, Elad; Elian, Dan; Regev, Ehud; Guetta, Victor (Frontiers in Cardiovascular Medicine, 2021)
BACKGROUND: Small proportion of patients in need of transcatheter aortic valve replacement (TAVR) do are not suitable for transfemoral approach due to peripheral artery disease. Alternative TAVR approaches are associated with short and long term hazards. A novel technique of caval-aortic (transcaval) access for TAVR has been utilized as an alternative access technique. AIM: To compare safety and efficacy of transcaval access as compared to other alternative access (axillary or apical) for TAVR. METHODS: Retrospective analysis of consecutive patients undergoing alternative access for TAVR in a single center. Events were adjudicated according to VARC-2 criteria. RESULTS: A total of 185 patients were included in the present analysis. The mean age of this cohort was 81 years with a small majority for male gender (54%). Of the entire cohort 20 patients (12%) underwent transcaval TAVR, and 165 patients (82%) underwent TAVR using alternative access. Overall baseline characteristics were comparable between the two groups. General anesthesia was not utilized in transcaval patients, however was routinely used in nearly all alternative access patients. TAVR device success was comparable between the two groups (95%). Acute kidney injury occurred significantly less frequently among transcaval patients as compared to alternative access patients (5% vs. 12%, p=0.05). Hospital stay was shorter for transcaval patients (6.3 days versus 14.4; p<0.001). No difference in early or 30-day mortality (10% vs. 7.9%, p=0.74) was noted between groups. CONCLUSIONS: In patients who cannot undergo TAVR via the trans-femoral approach due to peripheral vascular disease, transcaval access is a safe approach as compared to other alternative access techniques, with lower risk of kidney injury and shorter hospital stay.